Vulnerable plaques and patients: state-of-the-art. (13th May 2020) - Tomaniak, Mariusz; Katagiri, Yuki; Modolo, Rodrigo; de Silva, Ranil; Khamis, Ramzi Y; Bourantas, Christos V; Torii, Ryo; Wentzel, Jolanda J; Gijsen, Frank J H; van Soest, Gijs; Stone, Peter H; West, Nick E J; et al.
Abstract: Despite advanced understanding of the biology of atherosclerosis, coronary heart disease remains the leading cause of death worldwide. Progress has been challenging as half of the individuals who suffer sudden cardiac death do not experience premonitory symptoms. Furthermore, it is well-recognized that also a plaque that does not cause a haemodynamically significant stenosis can trigger a sudden cardiac event, yet the majority of ruptured or eroded plaques remain clinically silent. In the past 30 years since the term 'vulnerable plaque' was introduced, there have been major advances in the understanding of plaque pathogenesis and pathophysiology, shifting from pursuing features of 'vulnerability' of a specific lesion to the more comprehensive goal of identifying patient 'cardiovascular vulnerability'. It has been also recognized that aside a thin-capped, lipid-rich plaque associated with plaque rupture, acute coronary syndromes (ACS) are also caused by plaque erosion underlying between 25% and 60% of ACS nowadays, by calcified nodule or by functional coronary alterations. While there have been advances in preventive strategies and in pharmacotherapy, with improved agents to reduce cholesterol, thrombosis, and inflammation, events continue to occur in patients receiving optimal medical treatment. Although at present the positive predictive value of imaging precursors of the culprit plaques remains too low for clinical relevance, improving coronary plaque imaging may be instrumental in guiding pharmacotherapy intensity and could facilitate optimal allocation of novel, more aggressive, and costly treatment strategies. Recent technical and diagnostic advances justify continuation of interdisciplinary research efforts to improve cardiovascular prognosis by both systemic and 'local' diagnostics and therapies. The present state-of-the-art document aims to present and critically appraise the latest evidence, developments, and future perspectives in detection, prevention, and treatment of 'high-risk' plaques occurring in 'vulnerable' patients.